Analisis Tindak Pidana Penipuan Perekrutan Tenaga Kerja Kontrak (Studi Kasus Laporan Polisi Nomor : LP/B/2501/X/2021/SPKT/SATRESKRIM/Polres Metro Bekasi Kota/Polda Metro Jaya) - Resti Ayu Sumadi; Imam Budi Santoso (Widya Yuridika, 2022)
This criminal act of contract labor fraud in the Bekasi City Government occurs because people want to choose a fast or instant way to get the job they want, and the perpetrator takes advantage of this situation to become a broker, by paying a sum of money to the broker and the job, but in fact it is a scam. Because the Bekasi City Government insists that there is no requirement to give money to become a Contract Worker. This case continues to occur, because of the lack of handling of these problems, all perpetrators are not given legal firmness for their actions. The purpose of this paper is to analyze cases of criminal acts of contract labor crimes committed by employees of the Bekasi City Government. The research method used is descriptive qualitative research method. Qualitative research is in the form of research with a case study approach, and also uses a normative juridical approach, where this research is carried out in the literature by collecting secondary data consisting of primary, secondary, and tertiary legal sources. The case study in this article is taken from Police Report Number: LP/B/2501/X/2021/SPKT/SATRESKRIM/Polres Metro Bekasi City/Polda Metro Jaya. The Bekasi City Government should be able to provide law enforcement to the perpetrators in order to make perpetrators, and anticipate more problems that occur in the Bekasi City Government.